2021
DOI: 10.1177/10608265211042794
|View full text |Cite
|
Sign up to set email alerts
|

“Something You Just Don’t Talk About”: An Analysis of Teenage Boys’ Experiences of Non-Consensual Sexting in Lower Secondary School

Abstract: The current study explores Swedish teenage boys’ exposure to non-consensual sexting, drawing on interviews with ninth-grade students, age 14 to 15 years, in a lower secondary school in northern Sweden. The results reveal that boys are exposed to unsolicited “dick pics,” unsolicited “female nudes” and non-consensual “explicit video” sharing via the social media platform Snapchat. However, traditional notions of heteronormativity and heterosexual masculinity prevented boys from talking about, understanding and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A safe relationship with the primary caregivers in teens' lives and adequate, respectful relationship education in adolescence may potentially facilitate help-seeking among young persons. Research conducted among teenagers revealed that the latter often refrained from discussing their upsetting sexting experiences with adults (teachers, parents, authorities) due to the fear of consequences, including managing their parents' negative emotions in response to sexting incidents, intrusive monitoring of technology use, and blaming the young persons for what occurred (Hunehäll Berndtsson 2022). This constitutes a missed opportunity for adults to educate their children and teenagers about the nature of consensual and non-consensual online sexual interactions.…”
Section: "I Did Not Realise It Was a Violation"mentioning
confidence: 99%
“…A safe relationship with the primary caregivers in teens' lives and adequate, respectful relationship education in adolescence may potentially facilitate help-seeking among young persons. Research conducted among teenagers revealed that the latter often refrained from discussing their upsetting sexting experiences with adults (teachers, parents, authorities) due to the fear of consequences, including managing their parents' negative emotions in response to sexting incidents, intrusive monitoring of technology use, and blaming the young persons for what occurred (Hunehäll Berndtsson 2022). This constitutes a missed opportunity for adults to educate their children and teenagers about the nature of consensual and non-consensual online sexual interactions.…”
Section: "I Did Not Realise It Was a Violation"mentioning
confidence: 99%
“…A study focusing on male students, aged 14–15 and attending a lower secondary school in Sweden, found that traditional gendered perceptions of ‘male perpetrators’ and ‘female victims’ are so embedded in society that the boys interviewed did not understand that boys could be victims of digital sexual harassment just like girls, despite being exposed to both unsolicited dick pics and unsolicited female nudes; images they perceived as unpleasant. The study highlighted male vulnerability in youth sexting culture (Hunehäll-Berndtsson, 2022).…”
Section: The Phenomenon Of ‘Dick Pics’mentioning
confidence: 99%
“…In recent research, the societal phenomenon of dick pics—the practice of sending both solicited and unsolicited images of the male genitalia—has increasingly been investigated (e.g., Marcotte et al, 2021; Oswald et al, 2020; Passonen et al, 2019; Ravn et al, 2021; Ricciardelli & Adorjan, 2019; Ringrose et al, 2021b; Waling & Pym, 2019). However, there is a lack of research examining boys’ perspectives on unsolicited dick pics (Hunehäll-Berndtsson, 2022; Ricciardelli & Adorjan, 2019; Ringrose et al, 2021b). Hence, it is important to examine teenage boys’ views on unsolicited dick pics by looking at the phenomenon in relation to everyday school life.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some men may experience anxiety about the possibility of being perceived as feminine, gay, weak, and/or a variety of other negatively-associated characteristics (by both individual men and the generalized other) depending upon characteristics like their own internalized homophobia, their own beliefs in traditional sex roles, and a variety of other contextual cues and attributional processes that influence their thinking (Durón Delfin & Leach, 2022). In fact, recent work on texting looks at the idea of heterosexuality and gender as intrinsically entwined, noting that young people might struggle in disentangling the concepts and therefore struggle with threats to their own identity through messaging practices (Hunehäll Berndtsson, 2021).…”
Section: Introductionmentioning
confidence: 99%